The Potential of a Narrative and Creative Arts Approach to Enhance Transition Outcomes for Indigenous Australians Following Traumatic Brain Injury. Issue 2 (31st July 2019) - Bohanna, India; Fitts, Michelle; Bird, Katrina; Fleming, Jennifer; Gilroy, John; Clough, Alan; Esterman, Adrian; Maruff, Paul; Potter, Martin
Abstract: Background: Increasingly, narrative and creative arts approaches are being used to enhance recovery after traumatic brain injury (TBI). Narrative and arts-based approaches congruent with Indigenous storytelling may therefore provide benefit during the transition from hospital to home for some Indigenous TBI patients. This qualitative study explored the use and impact of this approach as part of a larger, longitudinal study of TBI transition with Indigenous Australians. Method: A combined narrative and arts-based approach was used with one Indigenous Australian artist to describe his transition experiences following TBI. Together with the researchers and filmmaking team, the artist was involved in aspects of the process. The artist contributed two paintings, detailing the story of his life and TBI. Based on the artworks, a film was co-created. Following the viewing of the film, impacts of the narrative and arts-based process were examined through semi-structured interviews with the artist, a service provider and a family member. Multiple sources of data were used in the final thematic analysis including transcripts of the interviews and filming, paintings (including storylines) and researcher notes. Results: Positive impacts from the process for the artist included positive challenge; healing and identity; understanding TBI and raising awareness. Discussion: This approach may enable the individual to take ownership over their transition story and to make sense of their life following TBI at a critical point in their recovery. A combined narrative and arts-based approach has potential as a culturally responsive rehabilitation tool for use with Indigenous Australians during the transition period following TBI.